Development of Interactive Digital Modules Based on Local Wisdom of Gandrung Lombok Dance on Plane Figures Material - Erna Anggraini; Djuita Hidayati (Journal La Edusci, 2026)
Integrating cultural contexts into mathematics learning has increasingly been recognized as an effective strategy to enhance students’ conceptual understanding and engagement. However, the incorporation of local cultural resources into digital learning media remains limited, particularly in mathematics education. This study aims to develop an interactive digital learning module based on the local wisdom of the Gandrung Lombok dance to support the teaching of plane geometry concepts. The research employed a Research and Development approach using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The study involved 32 third-semester students of the Primary School Teacher Education Program at Universitas Islam Negeri Mataram. Data were collected using expert validation sheets and user response questionnaires and were analyzed using quantitative descriptive analysis through percentage calculations. The results indicate that the developed module is highly feasible for instructional use. Expert validation of the learning material reached 95.83%, while media validation achieved 92.86%, both categorized as highly feasible. Lecturer response reached 95.25%, while student response reached 98.50%, indicating a very high level of user acceptance. These findings demonstrate that integrating cultural elements from the Gandrung Lombok dance into a digital learning module has strong pedagogical potential to support plane geometry learning while providing a culturally relevant and contextual learning experience.